"Reanalysis" Is Raising to Object. (2nd November 2015) - Drummond, Alex; Kush, Dave
Abstract: We propose a Case‐driven account of the "reanalysis" operation assumed by some researchers to underlie pseudopassivization. Contra previous analyses, we argue that reanalyzed prepositions do not form a unit with the verb at any level of representation. Rather, reanalyzed prepositions raise to a v/V‐medial Agr head, and the complement of the preposition raises to the specifier of this complex head to receive Case. This places the erstwhile complement in essentially the same structural configuration as an ordinary direct object, so that passivization proceeds normally. Preposition stranding, although it does not require reanalysis as such, is tied to one of the prerequisites for reanalysis: the presence of independent Agr projections. This explains why all languages with pseudopassives also permit preposition stranding. Reanalysis also accounts for certain instances of anaphoric binding in the apparent absence of c‐command.